2023
DOI: 10.3390/insects14030270
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone Aerosol Emitters for Lobesia botrana Mating Disruption in Italian Vineyards

Abstract: Despite the great amount of information on the European Grapevine Moth (EGVM), Lobesia botrana (Lepidoptera: Tortricidae), and the effective strategies available for its management, this moth remains the main key pest damaging grapevines in the Mediterranean and Central Europe wine-growing areas. Synthesizing and manipulating its sex pheromone components fostered the development of new dispensers to boost the effectiveness and sustainability of mating disruption (MD) programs. Recent MD research has highlighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, the MD formulations should be effective in cases of high pest population densities under different climatic conditions (Ioriatti et al 2011 ; Lucchi et al 2019b ). For EGVM, previous studies reported the effectiveness of MD strategies against this species, with different kind of dispensers (e.g., ampulla and capillary tube) and pheromone release modalities (e.g., active or passive release devices) (Altindisli et al 2016 ; Benelli et al 2023c ; Gordon et al 2005 ; Ioriatti et al 2011 ; Lucchi et al 2018a ). In our trials, the experimental dispenser proved to be effective at all densities tested, showing a comparable reduction in EGVM infestation levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the MD formulations should be effective in cases of high pest population densities under different climatic conditions (Ioriatti et al 2011 ; Lucchi et al 2019b ). For EGVM, previous studies reported the effectiveness of MD strategies against this species, with different kind of dispensers (e.g., ampulla and capillary tube) and pheromone release modalities (e.g., active or passive release devices) (Altindisli et al 2016 ; Benelli et al 2023c ; Gordon et al 2005 ; Ioriatti et al 2011 ; Lucchi et al 2018a ). In our trials, the experimental dispenser proved to be effective at all densities tested, showing a comparable reduction in EGVM infestation levels.…”
Section: Discussionmentioning
confidence: 99%
“…kurstaki and aizawaii (Benelli et al 2023a ; Civolani et al 2014 ). The understanding of the courting and mating behavior of EGVM mediated by pheromone blends, now synthesized and formulated, has led to the consolidation and improvement of MD techniques to manage this key pest (Benelli et al 2023a ).…”
Section: Introductionmentioning
confidence: 99%